The impact of receiving price and climate information in the agricultural sector (2010)
Previous studies indicate that Colombian farmers make production decisions based on informal sources of information, such as family and neighbors or tradition. In this paper we randomize recipients of price and climate information using text messages (SMS technology). Under this experimental design we find that relative to those farmers who did not receive SMS information, the farmers that did had better knowledge of prices and the dispersion in the expected price of their crops was narrower, although we do not see a significant difference in the actual sale price. Farmers also report that text message information is useful and becomes an important source of information for sales. Even though we find significant reduction in crop loss in general and due to weather conditions, we do not find significant changes in their revenues or household expenditures.